NEOLOGISMS AND THEIR ROLE IN MODERN LEXICOGRAPHY - Roza Bahodirova; Lobar Baxodirova (TADQIQOTLAR, 2026)
Abstract Neologisms are newly created words, expressions, or meanings that appear in a language as society, technology, culture, and communication continue to develop. In lexicography, neologisms are important because dictionaries must constantly adapt to linguistic change and include new vocabulary used by speakers. This article discusses the  concept  of  neologisms,  their  classifications,  formation  processes,  and  their significance in  modern  lexicography.  The  study  also  examines  how  lexicographers identify and record neologisms in dictionaries and how globalization, social media, and technological  innovation  contribute  to  lexical  expansion.  The  article  highlights  the importance of neologisms in enriching language and reflecting social transformation.